La rivoluzione teatrale di Laurent Chétouane - Heeg, Günther (Kritik. Rivista di letteratura e critica culturale, 2024)
Laurent Chétouane is the quietest revolutionary playwright in German theater. Since the beginning of this millennium, Chètouane has been staging highlights of the German public theater canon in the German public theater system and in other European theatres. This essay aims to illustrate how in his representations, the focus is equally on the bodily reality of text and spoken word and the textuality of bodies in motion. Chètouane describes the turning point in his work that came about through collaboration with dancers and the relationship with the body not dancing, but moving. At the beginning lies the question of how “what is said [...] exerts an influence on space. And how it exerts an influence on bodies”.